DETERMINANT OF ISLAMIC FINANCIAL INCLUSION IN DIGITAL ERA: CROSS-PROVINCE ANALYSIS - Abdullah, Zaki; Saleh, Samsubar; ., Mujiyati (UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
In recent years, the Islamic financial sector has become one of the most vital sectors in the Islamic economic system in Indonesia. Therefore, more attention needs to be paid to the measurement of Islamic financial inclusion and its and policy making, especially in facing the digitalization of economy, because the digitalization can be a momentum that provides opportunities as well as threats to Islamic finance. This study attempts to measure Islamic financial inclusion at the provincial level in Indonesia through the dimensions of accessibility, availability and utilization and analyzes the impact of digitalization on Islamic financial inclusion. Measurements are made using the Sarma Index, while the analysis of the impact of digitalization on Islamic financial inclusion employs the fixed effect model on the balanced panel data. The measurement results show that developed provinces tend to have higher levels of Islamic financial inclusion compared to developing provinces. Furthermore, provinces with a Muslim majority have a higher level of Islamic financial inclusion compared to provinces with a Muslim minority populations. In the panel data analysis, it was found that internet penetration has a negative and significant effect on Islamic financial inclusion, which shows that the majority of people in Indonesia still use the internet to access entertainment content and that internet use has not been optimized to access financial services. Nevertheless, the presence of the Islamic fintech platforms has a significant positive effect on Islamic financial inclusion in Indonesia. The variable level of cell phone usage has no significant effect on the level of Islamic financial inclusion and the average length of schooling has a significant negative effect on Islamic financial inclusion.